Rolling with the Punches: Why It Is Ethical to Practise 'Death Knocks'. (June 2016) - Barnes, Lyn; Tupou, Janet; Harrison, Jacqueline
With journalism ethics increasingly coming under scrutiny, it can seem incongruous that editors continue to expect novice journalists to carry out 'death knock' stories, where they are expected to interview the victim's next of kin to find out more about the person. Journalism students are seldom trained in how to deal with these sensitive interviews, instead, most practise on the public. Simple role-play exercises at Auckland University of Technology—using professional actors—highlight the significance of students 'winging' it. The lack of training for challenging but routine duties including death knocks can lead to emotional exhaustion, burn out and a greater chance of victims being retraumatized. This article focuses on the concept of emotional labour (Hochschild, 1983, The managed heart: Commercialization of human feeling. Berkeley: University of California Press) and how it can affect journalists. According to Hochschild, emotional labour refers to the process by which people are expected to manage their feelings in accordance with work-defined rules and guidelines. In other words, this term describes the strategies that people adopt and that go beyond physical or mental duties. It is increasingly important that educators consider emotional labour, not only for the sake of graduates who will cover traumatic events but also for the reputation of journalism as a profession.